Different extenders in the cryopreservation of bovine epididymal spermatozoa - Papa, Patrícia M. [UNESP]; Papa, Frederico O. [UNESP]; Oliveira, Letícia A.; Guasti, Priscilla N. [UNESP]; Castilho, Caliê; Giometti, Ines Cristina (Elsevier B. V., 2015)
The objective of this study was to evaluate the effects of two different egg yolk extenders incubated with or without Sperm Talp on the motility and plasma membrane integrity of cryopreserved bovine epididymal spermatozoa after freezing. Twenty-five testicles with epididymides from mature bulls were collected at the abattoir. Epididymal sperm recovery was performed by retrograde flushing using a skim milk-extender (Botu-Semen™). After recovery, sperm were incubated either without or with Sperm Talp and then submitted to centrifugation. For the freezing process, half of the testes were processed with Tris egg yolk extender, and half were processed with Botu-Bov™ egg yolk extender. Samples incubated in Sperm Talp exhibited better results than epididymal spermatozoa that were incubated without Sperm Talp (p<0.05). Both Botu-Bov™ and Tris could be utilised to freeze sperm from the bovine epididymides if the sperm were previously incubated with Sperm Talp. The extenders examined in this work did not differ in their effect on plasma membrane integrity after freezing.
Keywords: Sperm Talp; Semen extender; Epididymal spermatozoa; Bull; Cryopreservation